Pengembangan E-Modul Sistem Koloid dengan Contextual Teaching and Learning (Ctl) Berorientasi Chemo-Entrepreneurship (Cep) untuk Meningkatkan Kemampuan Berpikir Kritis Peserta Didik - Maifil Dwi Andrean; Rahadian Zainul; Umar Kalmar Nizar; Desy Kurniawati (Jurnal Penelitian Pendidikan IPA, 2024)
The high unemployment rate among high school graduates and the low critical thinking ability of high school students motivated the author to develop electronic teaching materials based on a contextual approach and oriented toward entrepreneurship. This study aims to determine the validity, practicality, and effectiveness of the e-Module on colloid system with Contextual Teaching and Learning (CTL) oriented toward Chemo-Entrepreneurship (CEP) to enhance students' critical thinking ability. The research method employed is Research and Development (R&D) using the Plomp model, which consists of the preliminary research phase, development or prototyping phase, and assessment phase. The research instruments used include validity questionnaires, practicality questionnaires and critical thinking ability test. The e-Module was validated by three lecturers from the Chemistry Department at UNP and two chemistry teachers from SMAN 6 Solok Selatan. Practicality testing was conducted with two chemistry teachers and 30 eleventh-grade students from SMAN 6 Solok Selatan. Data obtained from the validity and practicality tests were analyzed using Aiken’s V formula and practicality percentages. The validity test results showed a V value of 0.92, indicating a valid category. The analysis of the teacher practicality questionnaire showed an 86% score, categorized as very practical, while the student practicality questionnaire showed an 81% score, categorized as practical. The t-test yielded a sig (2-tailed) value of 0.026. Based on these results, it can be concluded that the developed e-Module is valid, practical, and effective in enhancing students' critical thinking skills.